Reducing Dysmenorrhea in Adolescent Girls with Yoga and Benso Relaxation - Karnilan Lestari Ningsi Sam; Dewi Ari Sasanti (Indonesian Journal of Global Health Research, 2026)
The majority (70-93%) of adolescents experience discomfort related to menstruation. It has been reported that 90% of menstruating adolescents experience menstrual pain, and 21% of these experience severe pain. Their quality of life and participation in school, sports, and social activities are all affected. Dysmenorrhea leads to decreased quality of life, absenteeism, and an increased risk of depression and anxiety. Up to half of patients with dysmenorrhea miss school or work at least once, and 10% to 15% experience regular absences during menstruation. To find out decrease in dysmenorrhea in adolescent girls with yoga and Benson relaxation. Using the true experimental design method using one group design, pretest-posttest design, sampling technique using purposive sampling. The number of samples in this study is 30 samples. The adolescent girls' dysmenorrhea scale was measured using the Numeric Rating Scale (NRS) before and after treatment, data analysis is carried out univariately to describe the frequency distribution and bivariately using the Wilcoxon test. The results of the Wilcoxon signed rank test statistical test show a value of ρ < 0.001, which means that there is a decrease in dysmenorrhea in adolescent girls with yoga and Benson relaxation. Decrease in dysmenorrhea in adolescent girls with yoga and Benson relaxation.